2019
DOI: 10.3390/nu12010091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Ingestion of Quercetin-Rich Onion Powder for 12 Weeks on Visceral Fat: A Randomised, Double-Blind, Placebo-Controlled, Parallel-Group Study

Abstract: Quercetin, which is frequently found in vegetables such as onion, is widely found to have biological activities such as visceral fat reduction. Therefore, we performed this randomised double-blind placebo-controlled parallel-group study and analysed the effects of daily intake of quercetin-rich onion on visceral fat for 12 weeks. Seventy healthy Japanese subjects whose body mass index (BMI) was ≥23 and <30 were recruited and randomly assigned to either the quercetin-rich onion group or placebo group. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…[ 12 ]. Nishimura et al reported that the daily intake of onion rich in quercetin might improve liver function and have anti-obesity effects [ 13 ]. Due to the structural functionalities, quercetin has maximum radical scavenging activity and acts as a potent antioxidant, representing the main antioxidative flavonol in the human diet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ]. Nishimura et al reported that the daily intake of onion rich in quercetin might improve liver function and have anti-obesity effects [ 13 ]. Due to the structural functionalities, quercetin has maximum radical scavenging activity and acts as a potent antioxidant, representing the main antioxidative flavonol in the human diet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Onions as a common food have been the subject of numerous clinical trials, only few side‐effects have been reported. Nishimura et al (Nishimura et al., 2019) reported four participants with mild gastrointestinal symptoms. In Song et al's study, two patients experienced transient itching after using the onion extract gel (Song et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration with 150 mg/day quercetin for six weeks decreases systolic blood pressure (SBP) and plasma oxidized LDL (ox-LDL) concentrations [ 26 ], and in women with T2D, oral 500 mg/day quercetin significantly reduced the serum concentration of tumor necrosis factor α (TNF-α) and IL-6, as well as SBP [ 27 ]. Even at low doses of 60 mg/day, quercetin still reduced visceral fat and serum alanine transaminase (ALT) [ 28 ]. However, Verena Brüll et al reported a test of ineffective quercetin administration in overweight-to-obese patients with pre- and stage I hypertension [ 29 ], which may be related to the shorter treatment cycle and lower dosage.…”
Section: Flavonoidsmentioning
confidence: 99%